Upaya Meningkatkan Kemampuan Membaca Qur’an Dengan Metode Iqra’ - zuriah zuriah (GHIROH, 2022)
This article is focused on discussing efforts to improve the ability to read Al-Qur'an Surah Al Mujdah/58:11 and Surah Ar Rahman/55:33 using the Iqra' method. This study aims to determine the extent to which the ability to read the Qur'an of seventh grade junior high school students in Islamic Religious Education lessons in the material of Surah Al Mujdah/58:11 and Surah Ar Rahman/55:33 is increased. To answer these problems, the research conducted is classroom action research. The results of the data analysis showed that students who had not yet completed learning to read the Qur'an experienced a significant increase after the action was taken. This is due to the use of the Iqro 'method consisting of six volumes starting from a simple level, step by step to a perfect level. So that students are able to improve their ability to read the Qur'an well.